Strategi Adaptif Tukang Becak dalam Bertahan Hidup di Pantai Losari Kota Makassar - Syifa Shafira; Mrs. Nurlela; Mr. Ahmadin (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to examine and analyze the socio-economic life of a pedicab driver in Losari Beach and adaptive strategies to meet their daily needs. This research is a qualitative research which is analyzed and written descriptively. Data collection techniques were carried out using the methods of observation, interviews, and documentation by involving 10 (ten) individuals as informants. The results of this study indicate that the socio-economic life of a pedicab driver on Losari beach is currently very worrying. This shows that the income as a pedicab driver in a day is not fixed. The distance traveled and the hours worked determine their income because the longer they work, the more likely they are to earn. The adaptive strategies of pedicab drivers on Losari beach in fulfilling their lives are decreasing with the presence of several types of public transportation such as online motorcycle taxis. The shift of customers from rickshaws to online motorcycle taxis is very detrimental to pedicab drivers. Adaptation strategies are essentially ways of survival that are carried out by everyone to be able to maintain their survival.